Analisis Kewajiban Notaris Dalam Memberikan Jasa Hukum Kepada Orang Yang Tidak Mampu - Sirojul Hakim, Muhammad Difa; Santoso, Budi (Law, Development and Justice Review, 2025)
Implementing good notary services can increase public trust in the notary institution itself. Reputation and trust are very important in the business world. However, not all people in Indonesia have the same economic capabilities, there are also less well-off people. Legal services in the notary sector are needed by all levels of society. Article 37 Paragraph (1) of the Law on the Position of Notaries states that Notaries must provide protection and guarantee legal certainty to the public regardless of the economic capacity of their clients. This research aims to determine the factors behind notaries providing free legal services to people who cannot afford it in accordance with Article 37 paragraph (1) UUJN, as well as to determine the legal consequences for notaries who do not carry out these obligations. The method used is a normative legal research method with a legal concept analysis approach and a legislative approach. The research results show that there are several factors behind notaries providing free legal services to people who cannot afford them, namely human factors, the notary's confidence, and the client's candor. These three factors encourage notaries to provide free legal services. In addition, if a notary does not provide free legal services to people who cannot afford it, the notary may be subject to sanctions. Acceptable sanctions include verbal warnings, written warnings, temporary dismissal, honorable dismissal, or dishonorable dismissal.